1991
DOI: 10.1111/j.1365-2249.1991.tb05787.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary IL-6: a marker for mesangial proliferative glomerulonephritis?

Abstract: SUMMARYA prospective study of plasma and urinary interleukin-6 (IL-6) levels was performed in 54 patients undergoing renal biopsy to determine whether detectable urinary IL-6 was a reliable marker for mesangial proliferation, Interleukin-6 was found in both the urine and plasma of seven patients, the urine alone of 15 patients, and the plasma alone of two patients. Interleukin-6 was not detected in the urine or the plasma ofthe remaining 30 patients, the urine of 10 healthy controls or the urine of 10 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…These findings raise the possibility that the scenario is autocrine, and the B-cell hyperactivity partly independent of T cell help. Claims have also been made [28] that urinary IL-6 is a marker for proliferative glomerulonephritis. This is not surprising, because infiltrating inflammatory cells, mainly monocytes and macrophages, could be the major source of IL-6 in the kidney of patients with lupus nephritis [29].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…These findings raise the possibility that the scenario is autocrine, and the B-cell hyperactivity partly independent of T cell help. Claims have also been made [28] that urinary IL-6 is a marker for proliferative glomerulonephritis. This is not surprising, because infiltrating inflammatory cells, mainly monocytes and macrophages, could be the major source of IL-6 in the kidney of patients with lupus nephritis [29].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…43,44) Increased IL-6 has also been detected in the urine and renal glomeruli of patients with lupus nephritis. 45) NZB and NZW F1 (B/WF1) mice spontaneously develop autoimmune disease that resembles human SLE, i.e., hypergammaglobulinemia, autoantibody production including anti-DNA antibody, immune complex-mediated glomerulonephritis, and death from renal failure. We and others previously reported that B cells from BWF1 mice in vitro show hyperresponsiveness to IL-6 and then produce anti-DNA antibody.…”
Section: Pathogenic Roles Of Il-6 In the Develop-ment Of Autoimmune Dmentioning
confidence: 99%
“…10,11 Urinary IL-6 stimulates proliferation of rat mesangial cells that produce IL-6 in vitro. 10 It has also been identified as a marker of renal IL-6 production, 12 yet elevated levels of IL-6 in urine have been found in 30-50% of patients with IgA nephropathy. 10,11 IL-6 may thus act as an autocrine growth factor in the mesangium and dysregulated production of IL-6 may be involved in the mesangial proliferation associated with glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%